Phytochemical Analysis and Antioxidant and Antidiabetic Activities of Extracts from Bergenia ciliata, Mimosa pudica, and Phyllanthus emblica - Basanta Kumar Sapkota; Karan Khadayat; Kabita Sharma; Bimal Kumar Raut; Dipa Aryal; Bijaya Bahadur Thapa; Niranjan Parajuli (Hindawi Limited, 2022)
Diabetes is a metabolic disorder of high blood sugar levels which leads to various chronic health-related complications. The digestive enzymes α-amylase and α-glucosidase play a major role in the hydrolysis of starch to glucose; hence, inhibiting these enzymes is considered an important strategy for the treatment of diabetes. Medicinal plants such as Bergenia ciliata, Mimosa pudica, and Phyllanthus emblica are commonly used in traditional remedies due to their numerous health benefits. This study aimed to determine the phytochemicals as well as TPC and TFC contents in these plant extracts along with their antioxidant and enzyme inhibitory activity against α-glucosidase and α-amylase. The ethyl acetate extracts of selected plants have shown higher TPC and TFC contents. The aqueous extract of B. ciliata (IC50: 16.99 ± 2.56 μg/mL) and ethyl acetate extract of P. emblica (IC50: 11.98 ± 0.36 μg/mL) and M. pudica (IC50: 21.39 ± 3.76 μg/mL) showed effective antioxidant activities. Furthermore, ethyl acetate extract of B. ciliata showed significant inhibitory activity against α-amylase and α-glucosidase with IC50 values of 38.50 ± 1.32 μg/mL and 3.41 ± 0.04 μg/mL, respectively. Thus, secondary metabolites of these medicinal plants can be repurposed as effective inhibitors of digestive enzymes.